The religious element in Mau Mau - Leakey, L. S. B. (International Library of African Music, 1954)
The Mau Mau leaders were very fully aware that the Kikuyu are by nature an intensely religious people, who could not do without a religion of some sort—people who needed the mental comfort of a “belief”. They knew too that among their own people there were hundreds of thousands who had lost all faith in the religion of their ancestors but who had never accepted Christianity except in a nominal way. The failure of so many to accept Christianity in a deep and real sense arose from the fact that the Christian mission churches had not been content to teach only the simple teaching of Christ but had added to them much that was not in the New Testament, but which was the doctrine of the particular mission or Christian sect to which they belonged. Nevertheless, these tens of thousands of nominal Christians were people who were well acquainted with the outward forms of Christian worship and who had attended church services, so the pattern was a useful one to use. This was more particularly so since this was also the pattern used by the separatist African churches which existed in the tribe, churches which were linked with the Independent Schools movement. And so the outward patterns of Christianity, hymn-singing, formal prayers, sermons, and the recitation of a creed, were adopted as the foundations of the Mau Mau religion, which was to draw the Kikuyu to the political cause of the Kikuyu Central Association.
Keywords: Hymns; Race relations; Kikuyu (African people); Ethnomusicology; Religion; Colonies; Colonisation; African Music; Mau Mau; Great Britain